1997
DOI: 10.3168/jds.s0022-0302(97)76156-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Forage Concentration and Buffer Addition on Duodenal Flow of Trans-C18:1 Fatty Acids and Milk Fat Production in Dairy Cows

Abstract: Milk fat depression in cows fed high grain diets has been shown to be related to increased trans-C18:1 fatty acids in milk. Trans-C18:1 fatty acids are produced as a result of incomplete biohydrogenation of dietary polyunsaturated fatty acids in the rumen. The objective of this study was to determine the effects of varying amounts of dietary concentrate and buffer addition on duodenal flow, apparent absorption, and incorporation of trans-C18:1 fatty acids into milk fat. Four ruminally and duodenally cannulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
123
9
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(158 citation statements)
references
References 20 publications
19
123
9
7
Order By: Relevance
“…Concentrate level did not significantly affect milk fat percentage, but compared with studies where milk fat depression has been reported [6,7], the concentrate:forage ratio in our study was rather low for both high and low concentrate diets (50:50 and 30:70, respectively). However, the total intake of starch appeared to be a major cause of variation in milk fat percentage (Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Concentrate level did not significantly affect milk fat percentage, but compared with studies where milk fat depression has been reported [6,7], the concentrate:forage ratio in our study was rather low for both high and low concentrate diets (50:50 and 30:70, respectively). However, the total intake of starch appeared to be a major cause of variation in milk fat percentage (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…A number of studies have demonstrated that increasing amounts of readily digestible carbohydrates in the diet are associated with increased proportions of trans10,cis12-CLA and trans10-C18:1 in milk fat [4][5][6]16]. The fact that the concentrate level only affected trans10,cis12-CLA and trans10-C18:1 but also the cis9,trans11-CLA and trans11-C18:1 concentration in milk when maize silage was fed, suggests that increased proportions of concentrate (starch) in the diet does not severely affect the ruminal biohydrogenation pattern unless combined with a forage naturally high in starch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans 18:1 isomers are formed during the penultimate step of rumen biohydrogenation of dietary 18-carbon PUFA to 18:0, with the isomer profile being dependent on the carbohydrate and lipid composition of the diet (Harfoot and Hazlewood, 1997). Kalscheur et al (1997) found that increasing the amount of dietary readily digestible carbohydrates caused an increase in certain milk trans 18:1. More specifically, studies have also found that complete replacement of GS with MS in the diet increases milk trans-10 18:1 concentrations (Shingfield et al, 2005;Ferlay et al, 2006;Nielsen et al, 2006).…”
Section: --mentioning
confidence: 99%
“…The concentrations of the intermediates in the rumen depends on the extent to which PUFA substrates are metabolized and are influenced by the initial concentration of dietary PUFA (Harfoot et al, 1973), passage rate, and rumen pH (Troegeler-Meynadier et al, 2003;Qiu et al, 2004). Altered rumen function resulting from a low rumen pH has been demonstrated to reduce the extent of PUFA biohydrogenation both in vitro (Martin and Jenkins, 2002) and in vivo (Kalscheur et al, 1997). As rumen pH is mainly influenced by the fermentable carbohydrate in the diet, it is possible that the amount and source of starch and or the rate of ruminal degradation of starch could play a role in altering rumen pH, which in turn could affect biohydrogenation intermediates in the rumen.…”
Section: Introductionmentioning
confidence: 99%